Road to Avonlea. The complete second season [videorecording (DVD)] = Les contes d'Avonlea. L'intégrale de la deuxième saison. - Polley, Sarah; Burroughs, Jackie; Ruffman, Mag; Montgomery, L. M. (Lucy Maud), 1874-1942 (Distributed by Sullivan Entertainment, Inc., 2009)
Sarah and her cousins continue to wreak havoc and land in trouble, much to the adults' dismay.